Recent Forest Cover Loss in the Core Zones of the Monarch Butterfly Biosphere Reserve in Mexico - Flores-Martínez, José Juan; Martínez-Pacheco, Anuar; Rendón-Salinas, Eduardo; Rickards, Jorge; Sarkar, Sahotra; Sánchez-Cordero, Víctor (Frontiers in Environmental Science, 2019)
The Monarch Butterfly Biosphere Reserve (MBBR) in central Mexico was established in 2000 to protect monarch butterfly (Danaus plexippus) overwintering colonies and contribute to the conservation of the monarch migratory phenomenon. The MBBR has faced forest cover losses due to illegal logging and climate-related factors. Here we report forest cover losses from 2012 to 2018 in the core zones of the MBBR where most monarch overwintering colonies perch. We used aerial ortho-photographs and satellite images complemented with field validation for temporal comparisons. During this period, 163.44 ha of forest cover were affected, 125.44 ha due to climate-related factors (rain and wind), 25.86 ha due to large-scale illegal logging, and 12.14 ha due to small-scale illegal logging. The core zone of the MBBR located in the State of Michoacan showed the highest forest cover loss values with 94.07 ha lost due to climate-related factors, and 38.0 ha lost due to illegal logging. Our study also showed a substantial decrease of 98% in large-scale illegal logging in the core zones of the MBBR compared to previous reported forest losses from 2001 to 2012. Forest cover loss was similar, yet the periods of the two studies differed, one 12 years in length, this one 6 years. The decrease of forest cover during the period studied suggests that factors elsewhere rather than forest cover loss in the monarch butterfly's winter habitat have strongly contributed to the dramatic population declines observed in monarch overwintering colonies since 2010.